Services as a new engine of growth for ASEAN, the People's Republic of China, and India - Ben Shepherd; Gloria Pasadilla (Asian Development Bank Institute (ADBI), 2012)
An increasing services orientation is likely to be a key feature of the economies of the Association of Southeast Asian Nations (ASEAN), the People's Republic of China, and India (collectively referred to as "ACI") over the medium-term. This paper aims to present a compendium of relevant data on the state of the services sector in the ACI countries, focusing on its contribution to overall economic activity, employment, and growth. To do this, it relies heavily on standard international sources, as well as national statistics in some cases. It also examines to the extent possible - given data restrictions - the services policy environment in the ACI countries, focusing on its implications for regional and international integration of services markets.
Keywords: O44; Q58; Q56; O10; O53; Q28; Q53; 330; services sector; services markets; economic development; emerging markets; middle income trap; Dienstleistungshandel; Regionale Wirtschaftsintegration; Dienstleistungssektor; Makroökonomischer Einfluss; Wirtschaftswachstum; China; Indien